Capsule endoscopy: Improving transit time and image view - Fireman, Zvi (World J Gastroenterol, 2005)
AIM: To evaluate the effect of various methods of small bowel preparation on the transit time and the quality of visualization of the entire small bowel mucosa. METHODS: Ninety-five patients underwent capsule endoscopy (CE) by easily swallowing the capsule. They were divided into three study groups according to the preparation used: group A (n = 26) by polyethylene glycol (PEG) liter or with sodium phosphate (SP) 12 h prior to the CE study; group B (n = 29) by erythromycin 1 h prior to the CE study; and group C (n = 40) without any preparation. Visualization ranged from good to satisfactory to poor. RESULTS: The gastric emptying time in the group prepared with erythromycin was shorter but without statistical significance and the small bowel transit time was unaffected. In elderly subjects prepared by PEG or SP, the gastric emptying time was significantly longer (163.7 min, P = 0.05). The transit times of the three sub-groups were not affected by gender or pathology. The grade of cleaning of the entire study group was 3.27 ± 1.1. The erythromycin group presented significantly the worst quality of images (P = 0.05) compared to the other sub-groups. Age, gender, and pathology had no effect on the quality of the cleaning of the small bowel in the sub-groups. One (1.05%) case had no natural excretion. CONCLUSION: Erythromycin markedly reduces gastric emptying time, but has a negative effect on the quality of the image in the small bowel. The preparation of elderly subjects with PEG or SP has a negative effect on the small bowel transit time.